Growth, thermal, vibrational studies and quantum chemical calculations of 2, 6-dibromo-4-nitrophenol: a new nonlinear optical crystal. (16th April 2017) - Sangeetha, K.; Guru Prasad, L.; Mathammal, R.
Abstract : Good-quality single crystals of 2, 6-dibromo-4-nitrophenol have been grown by slow evaporation solution growth technique using ethanol as solvent. The lattice parameters of the grown crystal were confirmed from single-crystal XRD analysis. Quantum chemical calculations were carried out using DFT /B3LYP/6-31 G(d, p) method. The optimized geometrical parameters have been obtained from the computational technique, and the result shows good agreement with the experimental XRD data. Both the experimental and theoretical vibrational spectrum confirms the presence of functional groups. Optical absorption behaviour of the grown crystal was examined by recording the optical spectrum and band gap energy was also estimated. Theoretical investigation shows that the title compound exhibits non-zero first-order hyperpolarizability values and has microscopic non-linear optical behaviour which is 22 times more than that of urea. The calculated HOMO and LUMO energies reveal the charge transfer characteristic of the title compound. Frequency conversion property of the grown crystal was investigated using Kurtz and Perry powder technique.